PEREMPUAN DALAM JERATAN EKSPLOITASI MEDIA MASSA - Syafrini, Delmira (Humanus, 2014)
Exploitation of women now comes in new faces; through the mass media. Media currently has a dual role, like two sides of a coin, on one side the media serves as a mediator for the improvement and progress of the nation, on the other side contributes to the suppression of media for the benefit of market capitalism toward consumer culture women once again being the subject of image construction. Expansion of the market and the mass media can not be separated from the flow of consumerism, because the mass media (particularly advertising on television) is an extension of the market to boost sales of industrial products in the form of imagery that originates from the "mode of production". Through the process of meaning people are affected by the image created by the market and advertisement that increase their consumptive behavior. Here begins the role of advertising in blurring the identity as the supporting tool of consumerism, therefore those who identify themselves as modern men are no longer themselves but apparently no more than "Robot Man" impersonator without original identity, the principle of life pawned in the name of modernity. Women are vying to look beautiful, to buy up all whitening products, hair straightener tools, body slimming drugs, making them "Paranoid" who are restless because being haunted by old age. Actually they are aware of the exploitation, but enjoy it on the pretext of style and fashion.Key words: women, exploitation, mass media